Effects of IV Acetaminophen on Core Body Temperature and Hemodynamic Responses in Febrile Critically Ill Adults: A Randomized Controlled Trial. Issue 7 (July 2017) - Schell-Chaple, Hildy M.; Liu, Kathleen D.; Matthay, Michael A.; Sessler, Daniel I.; Puntillo, Kathleen A.
Abstract : Objective: To determine the effects of IV acetaminophen on core body temperature, blood pressure, and heart rate in febrile critically ill patients. Design: Randomized, double-blind, placebo-controlled clinical trial. Setting: Three adult ICUs at a large, urban, academic medical center. Patients: Forty critically ill adults with fever (core temperature, ≥ 38.3°C). Intervention: An infusion of acetaminophen 1 g or saline placebo over 15 minutes. Measurement and Main Results: Core temperature and vital signs were measured at baseline and at 5–15-minute intervals for 4 hours after infusion of study drug. The primary outcome was time-weighted average core temperature adjusted for baseline temperature. Secondary outcomes included adjusted time-weighted average heart rate, blood pressure, and respiratory rate, along with changes-over-time for each. Baseline patient characteristics were similar in those given acetaminophen and placebo. Patients given acetaminophen had an adjusted time-weighted average temperature that was 0.47°C less than those given placebo (95% CI, –0.76 to –0.18; p = 0.002). The acetaminophen group had significantly lower adjusted time-weighted average systolic blood pressure (–17 mm Hg; 95% CI, –25 to –8; p < 0.001), mean arterial pressure (–7 mm Hg; 95% CI, –12 to –1; p = 0.02), and heart rate (–6 beats/min; 95% CI, –10 to –1; p = 0.03). Changes-over-time temperature, blood pressure, and heart rate outcomes were also significantly lower at 2 hours, but not at 4 hours. Conclusions: Among febrile critically ill adults, treatment with acetaminophen decreased temperature, blood pressure, and heart rate. IV acetaminophen thus produces modest fever reduction in critical care patients, along with clinically important reductions in blood pressure. Abstract : Supplemental Digital Content is available in the text.